PENGARUH FREE CASH FLOW, ENVIRONMENTAL AND SOCIAL DISCLOSURE TERHADAP NILAI PERUSAHAAN DENGAN GOVERNANCE DISCLOSURE SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Sektor Energi dan Bahan Baku yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2024) - Gamaliel Wira Santoso; Agus Purwanto (Diponegoro Journal of Accounting, 2026)
This study aims to analyze the effect of free cash flow, environmental disclosure, and social disclosure on firm value, as well as to examine the role of governance disclosure as a moderating variable. The study focuses on companies in the energy and basic materials sectors listed on the Indonesia Stock Exchange during the 2021–2024 period. These sectors were selected because they are characterized by high capital intensity, large investment requirements, and substantial exposure to environmental, social, and governance issues. This study employs a quantitative approach using secondary data obtained from financial statements, market data, and the Bloomberg ESG Database. The sampling technique used is purposive sampling, with the unit of analysis in the form of firm-year observations. The research data are structured as unbalanced panel data and analyzed using Moderated Regression Analysis (MRA) with a pooled regression approach through IBM SPSS Statistics. After the sample selection process and outlier treatment, the final sample consisted of 121 firm-year observations. The results show that free cash flow has a positive effect on firm value, while environmental disclosure has no effect on firm value. Social disclosure affects firm value, but in a negative direction. In the moderating analysis, governance disclosure does not moderate the effect of free cash flow on firm value, weakens the effect of environmental disclosure on firm value, and strengthens the effect of social disclosure on firm value. These findings indicate that market responses to financial and non-financial factors are selective, and that corporate governance plays different roles in shaping the relationship between sustainability disclosure and firm value.